1992
DOI: 10.1051/rnd:19920302
|View full text |Cite
|
Sign up to set email alerts
|

The influence of processing corn grain on glucose metabolism in ewes

Abstract: Summary ― Glucose metabolism was studied in ewes fed 800 g chopped alfalfa hay (H) or 400 g alfalfa hay and 400 g corn grain given in whole (HWC), ground (HGC) or extruded (HEC) form. Daily intake of metabolisable energy and crude protein were: 5.8 MJ, 109 g; 9.0 MJ, 84 g; 9.5 MJ, 84 g and 8.5 MJ, 88 g in H, HWC, HGC and HEC, respectively. In situ ruminal degradability ranked whole, ground, and extruded corn in ascending order. Ruminal pH and concentration of acetic acid were lower and of propionic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
2
18
3
Order By: Relevance
“…In these conditions, the irreversible glucose loss rate is the rate at which glucose leaves the sampled compartment never to return to that compartment, while the glucose entry rate is the rate of entry of glucose into the sampled compartment [56]. A combination of data from publications which compared different types of tracers [27,28,43] showed that on average glucose entry rates are 40% higher than the irreversible glucose loss rates.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, the irreversible glucose loss rate is the rate at which glucose leaves the sampled compartment never to return to that compartment, while the glucose entry rate is the rate of entry of glucose into the sampled compartment [56]. A combination of data from publications which compared different types of tracers [27,28,43] showed that on average glucose entry rates are 40% higher than the irreversible glucose loss rates.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The previous survey of the literature specifically indicated that the inclusion of maize in the diet improves glucose turnover. With maize based diets, rich in bypass starch, absorbed glucose may contribute to glucose turnover to a variable but sometimes to a considerable extent (up to 60% [23,27,31]). In beef steers fed dry-rolled sorghum, it was evaluated that glucose absorption from starch intestinal digestion could account on average for a third of the glucose metabolism [6].…”
Section: Glucose Precursors and Glucose Turnovermentioning
confidence: 99%
“…Landau et al (1992) found that the ruminal digestion of corn fed to sheep was 60% to 70% for whole grain and 78% to 80% for cracked grain. The starch not digested in the rumen passed to the intestine where it was mostly digested and could account for up to 50% of the glucose available in sheep fed whole or cracked maize (Landau et al, 1992).…”
Section: Levels Of Energymentioning
confidence: 99%
“…Landau et al (1992) found that the ruminal digestion of corn fed to sheep was 60% to 70% for whole grain and 78% to 80% for cracked grain. The starch not digested in the rumen passed to the intestine where it was mostly digested and could account for up to 50% of the glucose available in sheep fed whole or cracked maize (Landau et al, 1992). The resistance of the starch in maize to fermentation in the rumen makes this grain a potentially useful source of energy for feeding in the last week of pregnancy, especially if the starch that passes from the rumen is digested to glucose in the small intestine.…”
Section: Levels Of Energymentioning
confidence: 99%
“…Sheep fed maintenance level rations containing whole corn grain, which is moderately degradable in the rumen, had higher GER than sheep fed iso-energetic rations containing highly degradable extruded corn grain [8]. However, quite surprisingly, feeding extruded corn grain -at twice the maintenance level -to ewes bearing twin lambs during late pregnancy resulted in higher lamb birth-weights than feeding whole corn grain [10].…”
Section: Introductionmentioning
confidence: 89%